Pengaruh ESG dan Konservatisme Akuntansi terhadap Efisiensi Investasi - Rompas, Afril Yani; Sutandijo, Sutandijo (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) practices and Accounting Conservatism on Investment Efficiency in IDX ESG Leaders companies listed on the Indonesia Stock Exchange during 2019-2023. Investment inefficiency, often reflected in underinvestment or overinvestment, remains a concern in Indonesia as indicated by the high Incremental Capital Output Ratio (ICOR). To address this issue, this research provides empirical evidence on whether ESG disclosure and conservative accounting practices can enhance investment efficiency. Using a purposive sampling technique, 13 companies were selected from 30 ESG Leaders, resulting in 65 firm-year observations. Data were analyzed with panel data regression using EViews 12. The findings reveal that ESG and accounting conservatism jointly influence investment efficiency. However, ESG, measured by Bloomberg ESG scores, shows no significant individual effect. In contrast, accounting conservatism, proxied by accrual-based CONACC, significantly improves investment efficiency. These results suggest that conservative financial reporting provides stronger signals for optimal capital allocation than ESG disclosure alone. The study highlights theoretical implications for agency theory and practical insights for managers and regulators to balance sustainability practices with prudent accounting policies.